STRATEGI PENGEMBANGAN OBJEK WISATA PANTAI SELAT BARU OLEH DINAS KEBUDAYAAN, PARIWISATA, PEMUDA DAN OLAHRAGA DI KECAMATAN BANTAN KABUPATEN BENGKALIS TAHUN 2013 - ", SURBAYA; KHAIRANI, TUTI (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2014)
ABSTRACT The development of the tourism sector has considerable strategic prospects , as one of the sources of local revenue if developed optimally it is relevant to what is mandated by Law No. 32 of 2004 on Regional Government and Law No. 33 of 2004 Regarding Government Fiscal Balance and the Regional Center . In the law can be seen principally principle is set on the administration of local government that prioritizes the implementation of the principle of decentralization in the form of autonomy , real and responsible with regard to the potential and diversity of the region to achieve the purpose of the economy itself that is working to improve the service and welfare of the community . Strategy through the tourism department of local government and community participation are also considered to be able to bring in the strategy formulation development attraction . This study was conducted to determine the Coastal Tourism Development Strategy Object New Straits in Subdistrict Bantan Bengkalis Year 2013.The primary objective of this study was to identify Objects Tourism Development Strategy by the Office of the New Strait Budparpora in Bengkalis. This study belongs to the type of qualitative research using interview data collection technique is a direct communication with the research informants and conduct a question and answer related to the research problem. Object studied in this research is the official Budparpora Bengkalis as implementing tourism development strategy and all stakeholders who play an important role in the development of tourism in the New Straits Coast Bengkalis.Once identified, the results showed that the tourism development strategy should didikung Beach New Straits strategic development areas where there is cooperation between the managers discretion and implementing policies, improvement of infrastructure-oriented beach tourist attraction, tourism development strategies and environmentally friendly termanajerial management, as well as the development of tourism awareness groups and the formation of self-help groups were able to develop a wide range of business services that support a variety of tourism development in the New Straits Beaches.Keywords: Strategy Development, Tourism, Selat Baru Beach